Impact of Career Growth of Employees on Success of Small Scale IT Companies - et. al., Ashish Jain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present era is the era of competition; thus, employees of an organization have emerged as one of the greatest sources of competitive advantage. Employees can effectively contribute in building a sustainable competitive advantage for an organization. In this fast moving competitive world merely providing monetary benefits to the employees cannot ensure organizations success. Thus, a concept of employee career development is introduced to address the issues of personal growth of employees and for ensuring organizations success and performance enhancement. Current business market has totally accepted the fact that employees are the most determining factors accountable for success/failure because employees affect organizational productivity to a large extent. Career growth and career planning increases employee morale and thus help an organization to survive all the unforeseen external environmental conditions through skill enhancement. Therefore, this research aimed at analyzing the “programmer level employee’s career development and its effect on organization productivity, employee satisfaction, and factors associated with organization productivity etc. in SSIs (small scale industries) in IT sector”.